2015
DOI: 10.4172/2155-9899.1000341
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Signatures Identifying Different Stages of Latent Mycobacterium tuberculosis Infection and Discriminating Latent from Active Tuberculosis in Humans

Abstract: Objectives: One third of the world population is considered latently infected with Mycobacterium tuberculosis (LTBI) and sterilizing this reservoir of bacteria that may reactivate is required for tuberculosis (TB) elimination. The group of individuals with LTBI is heterogeneous with some of them being more at risk to develop TB disease than others. Improved diagnosis of subjects with LTBI is needed, allowing to differentiate subjects with LTBI from those with active TB, and to select among LTBI subjects those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…The diagnostic accuracy of this test was lower for disseminated compared to localized aTB, perhaps as a consequence of high immune suppression in disseminated aTB. A specific induction of CD8 + T cell responses by mycobacterial antigens during aTB is in line with previous reports (33, 34). The mechanisms of in vivo induction of these cells are still incompletely understood (33) This immunological signature was reported to be generated in response to a high bacillary load (35, 36), which was not always the case in our study, as less than half of children with aTB were culture confirmed.…”
Section: Discussionsupporting
confidence: 93%
“…The diagnostic accuracy of this test was lower for disseminated compared to localized aTB, perhaps as a consequence of high immune suppression in disseminated aTB. A specific induction of CD8 + T cell responses by mycobacterial antigens during aTB is in line with previous reports (33, 34). The mechanisms of in vivo induction of these cells are still incompletely understood (33) This immunological signature was reported to be generated in response to a high bacillary load (35, 36), which was not always the case in our study, as less than half of children with aTB were culture confirmed.…”
Section: Discussionsupporting
confidence: 93%
“…Since there are no early and accurate diagnostic tests currently available for detecting active TB and differentiate it from LTBI, immunodiagnostic biomarkers are urgently needed to monitor the progression from LTBI to clinical disease [9,28,29]. Studies [9,10,11,30,31] showed that one of the most promising biomarkers is HBHA. Although the existing studies explored the value of using IGRA with HBHA as a stimulating antigen to differentiate ATB from LTBI, they showed various results and it was difficult to obtain a consensus in deriving an accurate differential diagnosis [15,16,20,22,32].…”
Section: Plos Onementioning
confidence: 99%
“…A divergence was noted in the definition of the ATB groups between microbiologically confirmed TB and clinically confirmed TB. The inclusion of the LTBI groups had different selection criteria (TST or IGRA): the TST results are more often positive than the IGRAs, the LTBI groups in different studies exhibited varied risk stratifications [11,30,36,37]. Moreover, some studies specified neither the active TB type (pulmonary or extra-pulmonary TB) of the ATB subjects nor the treatment of the LTBI subjects.…”
Section: Plos Onementioning
confidence: 99%
“…It is estimated that 25% of the global population is latently infected with Mycobacterium tuberculosis, and 2 to 8% of these will develop the disease most of the time (50%) within the first 2 years after infection. Even though they are asymptomatic and do not transmit the infection, these subjects are a reservoir that sustains TB disease (3). Importantly, the risk of TB progression is much higher in children (30 to 40% progression rate if untreated) (4).…”
mentioning
confidence: 99%